Akta Perdamaian dan Pemulihan Ekologis: Analisis Tanggung Jawab Mutlak Korporasi dalam Kasus Kebakaran Lahan Gambut - Wulandari, Cici; Alissa, Evalina (Universitas Jambi, Fakultas Hukum, 2025)
This study aims to find out and analyze how the application of absolute responsibility (Strict Liability) contained in the peace deed regarding the restoration of peat ecosystems as compensation number 44/Pdt.G/LH/2021/PN and the legal consequences of non-implementation of the content of the peace agreement in the case of forest and land fires that occurred on the corporate land of PT. Pesona Belantara Persada and Pt. Putra Duta Indah Wood. The peeling method used in this thesis is Juridical-Empirical, where data collection and data processing are carried out empirically-normatively from factual data based on cases that occur and analyze cases based on applicable laws and norms. Based on the results of the research, the delay in the implementation of the verdict or peace deed that has been passed, the court can order the payment of forced money for each day of delay. Parties who have deliberately negligent and committed a default without an overmacht or force majure, have legal consequences that can be sanctioned in the form of paying losses suffered by other parties, cancellation of agreements, transfer of risks, and paying case costs if sued in court.